Biodiversity of megabenthos and coral reef condition in Tuan Island, Aceh Besar. Issue 1 (November 2021) - Dewiyanti, I; Mulyadi, M; Ulfa, M; Octavina, C; Haridhi, H A
Abstract: The existence of megabenthos has an important role in maintaining sustainability of coral reef ecosystems and in the food web process. Megabenthos is also often used as an indicator of the health condition of coral reefs. The purpose of study was to analyze the biodiversity of megabenthos associated with coral reef in Tuan Island. This research was conducted in July -September, 2020. There were four research stations determined by purposes method based on four wind directions. Megabenthos data collection carried out by benthos belt transect method and coral reef data collected by using the Line Intercept Transect (LIT) method. The results were found 8 species of megabenthos target, namely spiny starfish ( Acanthaster planci ), blue starfish ( Linckia laevigata ), sea urchins ( Diadema setosum ), sea cucumbers ( Holothuria atra ), clams ( Tridacna squamosa ), Drupella snails ( Drupella sp.), lola clams ( Tronchus niloticus ) and lobster ( Panulirus versicolor ). Totally, there were 190 individuals of megabenthos with the abundance ranged from 0.18 to 0.52 individuals/m 2 . Diadema setosum had the highest abundance with the value 0.9 individuals/m 2 followed by Drupulella sp. (0.3 individuals/m 2 ). The highest diversity index was station 4 followed by station 3, 2, and 1 with the value of 2.21, 0.85, 0.64, and 0.41, respectively. The diversity index was categorized as low and medium. The average of evenness and dominance indices were 0.04 and 0.62, both was medium category. The highest percentage of coral cover was at station 1 followed by station 3, 4, and 2, the coral cover value were 50.44%, 29.20%, 18.14%, and 9.29%, respectively. The correlation (r) between the percentage of coral reef cover and megabenthos abundance has a positive correlation, but the level of correlation was low (0.215 %). The density of megabenthos on Tuan Island did not have a major influence on coral reef cover where the determination value (R 2 ) was 0.0462 which indicated that the megabenthos abundance was influenced by the percentage of coral reef cover only 4.62%.